USAGE OF COMPUTER PERIPHERAL HARDWARE FOR NON-COMMON TASKS SOLVING - Тупіцин, М. Ф.; Пальчик, В. В.; Степаненко І. O. (Science-based technologies, 2013)
In the beginning of the article there is given an overview and analysis of various types of computer mouse of the main manufacturers: Xerox, Logitech, Microsoft, Apple, Razer, 3D Connexion. Authors developed and patented two technical solutions which allow to solve actual for airspace industry tasks. In the article there are considered examples of non-common usage of computer mouse and web-camera. On the basis of these devices there were designed systems (flowcharts are also given in the article), which provide: 1). signaling about penetration into the predefined region, 2). control of illumination in the apartment.